Biochemical and hormonal profile of the amniotic fluid from Nelore calves conceived by different reproduction biotechnologies - Piagentini, Marcelo [UNESP]; Prestes, Nereu Carlos [UNESP]; Moya-Araujo, Carla Fredrichsen; Araujo, Gustavo Henrique Marques; Takahira, Regina Kiomi [UNESP]; Oba, Eunice [UNESP] (Pontificia Universidade Catolica do Parana - PUCPR, 2012)
This study aimed to quantify biochemical constituents and hormonal concentrations in the amniotic fluid of Nelore calves conceived by different reproduction biotechnologies. Sixty animals were used and divided into: 1 – Twenty Nelore cows pregnant of calves obtained by artificial insemination; 2 – Twenty cows pregnant with Nelore calves obtained by embryo transference; 3 – Twenty cows pregnant with Nelore calves obtained by in vitro production. During the expulsion phase, the amnion was punctured and 15 mL of fluid were collected. The biochemical evaluation was performed with commercial kits in accordance to the manufacturer’s recommendations. It was used the radioimmunoassay to assess the progesterone and testosterone levels. The statistical analysis used was the variance analysis and Tukey (5% significance level). Mean urea and creatinine when comparing the three groups showed that group 3 had higher values of these two metabolites, suggesting that the kidney maturity is suitable. For gamma-glutamyltransferase, group 3 had a lower value compared to group 1. This enzyme is related to metabolism, may be inferred that the metabolic activity is high in animal production in vitro. The glucose values did not differ between the groups, suggests that the maternal-fetal exchanges were suitable for the power supply to the fetus. Lower chloride concentration was showed in group 3. Sodium and potassium were found in greater quantities in group 3 when compared to other groups. There was no significant difference for the testosterone and progesterone. The results obtained in biochemical analysis can conclude that the renal and liver activity and maternal-fetal exchange are normal in the different groups.

O presente trabalho teve por objetivo quantificar a concentração dos constituintes bioquímicos e hormonal no líquido amniótico de fetos Nelore, oriundos de diferentes biotécnicas reprodutivas. Utilizaram-se 60 vacas gestantes divididas em: 1 – 20 vacas prenhes de bezerros oriundos de inseminação artificial convencional (IA); 2 – 20 vacas prenhes de bezerros oriundos de transferência de embriões (TE) e 3 – 20 vacas prenhes de bezerros oriundos de produção in vitro (PIV). Durante a fase de expulsão, o âmnion foi puncionado e colheram-se 15 mL de líquido amniótico. As determinações bioquímicas foram conduzidas por kits comerciais. A progesterona e a testosterona foram determinadas por meio de radioimunoensaio (RIA) em fase sólida. Empregou-se a análise de variância e teste de Tukey com 5% de significância. O teor de ureia e creatinina no G3 foi maior que nos outros grupos e significativo (p < 0,05) em relação ao G1. Para gamaglutamiltransferase (GGT), o G3 apresentou menor valor em relação ao G1 (p < 0,05). Os valores de glicose não diferiram entre os grupos. O cloreto apresentou maior concentração em G1 e G2 que no G3 (p < 0,05). O sódio e o potássio foram encontrados em maior quantidade no G 3 em relação aos demais grupos. Na análise hormonal não foi detectada diferença significativa para testosterona e progesterona. Pelos teores de ureia e creatinina, concluiu-se que a presença destes, sugere maturidade renal adequada, que a GGT (relacionada ao metabolismo animal) está elevada nos bezerros de produção in vitro e que os grupos tiveram a concentração de glicose adequada ao fornecimento de energia ao feto. Os resultados obtidos na análise bioquímica indicam que a atividade renal e hepática, além das trocas materno-fetal, está normal nos diferentes grupos.
Perfil bioquímico e hormonal do líquido amniótico de bezerros Nelore concebidos por diferentes biotecnologias
Keywords: Amniotic fluid; Laboratorial analyses; Nelore; Líquido amniótico; Análise laboratorial; Nelore